A simple, combined test can improve the diagnosis of autoimmune urticaria - Hajdu Kata; Irinyi Beatrix; Gyimesi Edit; Kapitány Anikó; Dajnoki Zsolt; Csörgő Sándorné Bata Zsuzsanna; Kinyó Ágnes; Kiss Filip; Gáspár Krisztián; Szegedi Andrea (2017)
The diagnosis of autoimmune chronic urticaria (AIU) is difficult. Autologous serum skin test (ASST) is a screening method to diagnose AIU and was first used by Grattan et al., and was standardized by Sabroe et al. One major limitation of ASST is that positivity can refer not just to the presence of functional autoantibodies against FcepsilonRIalpha or IgE, but other yet unidentified serum factors. Besides the advantages of ASST which are its fast and easy implementation and its cost, since its positivity alone cannot define AIU, other methods are needed to confirm the diagnosis of AIU. This article is protected by copyright. All rights reserved.